Effectiveness Spinach Crispy Snack Consume to Increase the Hemoglobin Level in Diabetic Patient - Abdul kadir; Nesi Novita; Saprianto Saprianto (Poltekkes Kemenkes Palembang, 2021)
Anemia or lack of blood is characterized by normal hemoglobin (Hb) levels, occurs in certain population groups including young women, pregnant and lactating women, and people with chronic diseases such as diabetes mellitus (DM) and others. Various kinds of food ingredients both from plants and animals that are useful for controlling hemoglobin levels, especially plants or animals that contain ferrous (Fe) can bind Hb in the blood. Among the plants that contain Fe are spinach vegetables with a composition of 9.2 mg/100gram. To determine the effect of spinach chips as a snack that is useful for increasing Hb levels, it is necessary to conduct research to believe in this hypothesis. The purpose of this study was to determine the effect of spinach chips on Hb levels in Diabetes Mellitus Patients at the Kadir Medika Clinic in 2020. The method used in this study was an experiment with a sample of 62 people consisting of a control group and an intervention group that had met the inclusion and exclusion criteria. The results of this study indicate that spinach chips can increase Hb levels in patients with diabetes mellitus after being consumed for 10 consecutive days. However, in carrying out this diet there is still non-adherence to the patient following the research procedure so they were excluded from this study. The place of this research was at the Kadir Medika Clinic which was held from September 2020 to November 2020 Conclusion of this study was that spinach chips were consumed in a certain amount and within a certain period of time. Certain substances can increase hemoglobin levels.